An automated system for correction of rules of transformation from universal networking language into natural language - Aram A. Avetisyan; Levon R. Hakobyan (АН Арм. ССР)
An approach to automated correction of UNL grammar rules is implemented. The development process of the rule sets could be made in a more effective way if some tools are used which can find the rules responsible for possible errors and make suggestions about its correction. Several definitions for the formalization of the transformation process and the algorithm for such kind of functionality are created. The implementation of the algorithm in the UNDL Platform and some examples are described.
Keywords: Mathematics; Computer software